Effects of flameless catalytic infrared radiation on stored-wheat insects and wheat quality - Khamis, Moses (Kansas State University, 2009)
Stored-grain insects were managed traditionally with grain protectants and the fumigant phosphine. Protectant use leads to undesirable pesticide residues on grain. Many stored-grain insects are resistant to grain protectants and phosphine. Therefore, novel technologies are needed in the future to replace traditionally used methods. Preliminary laboratory and pilot scale field trials have shown catalytic infrared radiation of 2.8 to 7 μm wavelength to be effective in killing insects associated with stored wheat. The effectiveness of catalytic infrared radiation in killing life stages of three economically-important stored-grain insects in hard red winter wheat were evaluated. Wheat (113.5 or 227.0 g) infested with eggs, various ages of larvae, pupae, and adults were exposed for 45 or 60 sec at a distance of 8.0 or 12.7 cm from the catalytic infrared emitter. Infested wheat samples unexposed to infrared radiation served as the control treatment. Temperatures attained by the wheat samples during infrared exposure were monitored continuously using a non-contact infrared thermometer. The three insect species tested were the lesser grain borer, Rhyzopertha dominica (F.); rice weevil, Sitophilus oryzae L.; and red flour beetle, Tribolium castaneum (Herbst). The life stages of R. dominica and S. oryzae developing within wheat kernels were age-graded using radiographic techniques. The mean temperatures attained by wheat at the various treatment combinations ranged from 80[degrees] to 114[degrees]C. Both the time-dependent temperature profiles and mean wheat temperatures were greater in 113.5 g of wheat, exposed at a distance of 8.0 cm from the infrared emitter for 60 sec. The most heat tolerant stage in R. dominica was the older larvae, whereas in S. oryzae it was the egg, and in T. castaneum it was the pupa. In general, older larvae of all three species were less susceptible to infrared radiation than young larvae. The differences in susceptibility among life stages of all species to infrared radiation decreased with an increase in the mean temperature attained, and temperatures ≥105[degrees]C were needed to obtain 98 to 100% mortality of all life stages. Exposure to catalytic infrared radiation at the temperatures used to disinfest wheat did not adversely affect wheat, flour, and baking quality.
Keywords: Infrared; insect; mortality; wheat; quality; Agriculture, Food Science and Technology (0359)